PERSEPSI ORANG TUA YANG MENIKAH DI USIA MUDA TENTANG PEMENUHAN KEBUTUHAN ANAK USIA DINI (Studi terhadap Pasangan Suami Istri di Kenagarian Salareh Aia Kecamatan Palembayan Kabupaten Agam) - Elvira, Nova - (Bimbingan dan Konseling, 2014)
The background of this reasearch is the parents who were married at a young age who have young childhood and still behave like teenagers and do not carry of this and responsibilities as parents. The purpose of research describe: Parents percepcition of physiological and psychological need fulfillment early chillhood. This research is descriptive qualitative research. Informants of this research are 3 of couple who married young and informants supporting 3 people are:2 person parents, grandmaother and 1 person aunt from the young childhood. Research data collected throungh interviews. Accuaracy of test data by using triangulation of data, data reduction, presentation and conclusion. Results of the research found that: 1) the perception of the parens who married at a young age about the fulfiment of, physiological early chilhood is not better, because the parents belive the childhood physiological needs are fed just enough setiety or hunger closes, regardless of childhoodâs nutritional needs. 2) the percepcition of people who get married at the young age about the fulfillment of psychological needs of early chilhood are less goad, because the parents believe the childhood needs affection are met by giving childhood pocket money.